The participation of a juvenile victim’s representative in criminal proceedings: procedural and forensic aspects - I. O. Iemets (Law and Safety)
The article identifies the procedural and forensic aspects of participation of an attorney-at-law engaged to represent the interests of a juvenile victim in criminal proceedings. Based on the generalization of theoretical developments of Ukrainian scholars, it is found that they prefer to study the problem of protection of rights and legitimate interests of a minor suspect or accused. At the same time, given the current trends in crime, it should be noted that it has a devastating impact on the psyche of children. Moreover, they are increasingly becoming victims of criminal offences, especially those involving violence. This has raised the challenge of ensuring proper protection and the best interests of the minor victim.